2016
DOI: 10.1097/gme.0000000000000571
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intravaginal dehydroepiandrosterone (DHEA) on moderate to severe dyspareunia and vaginal dryness, symptoms of vulvovaginal atrophy, and of the genitourinary syndrome of menopause

Abstract: The daily intravaginal administration of 0.50% (6.5 mg) DHEA (Prasterone) has shown clinically and highly statistically significant effects on the four coprimary parameters suggested by the US Food and Drug Administration. The strictly local action of Prasterone is in line with the absence of significant drug-related adverse events, thus showing the high benefit-to-risk ratio of this treatment based upon the novel understanding of the physiology of sex steroids in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(111 citation statements)
references
References 71 publications
3
104
0
4
Order By: Relevance
“…Studies have shown intravaginal DHEA to increase the vaginal maturation index and decrease vaginal pH without increasing the serum levels of estrogen above the postmenopausal range [Ibe and Simon, 2010;Witherby et al 2011]. In addition, results from two randomized double-blind placebo-controlled phase III clinical trial reported this therapy to exert beneficial effects across all four aspects of sexual function, including desire/interest, arousal, orgasm [Labrie et al 2009] and pain at sexual activity in postmenopausal women [Labrie et al 2016]. A Cochrane review [Scheffers et al 2015] analyzed the effectiveness and safety of administering DHEA to women with menopausal symptoms and found that it was associated with improvements, albeit small, in sexual function by contrast with placebo and HT.…”
Section: Androgensmentioning
confidence: 99%
“…Studies have shown intravaginal DHEA to increase the vaginal maturation index and decrease vaginal pH without increasing the serum levels of estrogen above the postmenopausal range [Ibe and Simon, 2010;Witherby et al 2011]. In addition, results from two randomized double-blind placebo-controlled phase III clinical trial reported this therapy to exert beneficial effects across all four aspects of sexual function, including desire/interest, arousal, orgasm [Labrie et al 2009] and pain at sexual activity in postmenopausal women [Labrie et al 2016]. A Cochrane review [Scheffers et al 2015] analyzed the effectiveness and safety of administering DHEA to women with menopausal symptoms and found that it was associated with improvements, albeit small, in sexual function by contrast with placebo and HT.…”
Section: Androgensmentioning
confidence: 99%
“…As observed after 12 weeks of treatment in the other clinical studies ERC-210 [30], ERC-231 [31], ERC-234 [32] and ERC-238 [33], as well as in the 1-week pharmacokinetic study ERC-213 [4,16,17], there was no biologically significant drug-related change in serum steroid concentrations following intravaginal administration of 0.50% prasterone. Such data are as expected from the intracrine mechanisms [5], which control sex steroid physiology at menopause and later by limiting any biologically active estrogen and androgen to the intracellular milieu which is the site of formation and inactivation of all sex steroids [6].…”
Section: Discussionmentioning
confidence: 43%
“…Since the decrease in the percentage of parabasal cells, the increase in the percentage of superficial cells and the decrease in vaginal pH are estrogen-responsive parameters [22], the benefits observed on these parameters as well as on dyspareunia [23,30,31,33], illustrate the intracellular formation of estrogens from DHEA in the vaginal mucosa. Most importantly, it shows that as required at menopause to protect the uterus and probably other tissues [6], the intracrine mechanisms permit tissuespecific intracellular formation, action and degradation of estrogens without systemic exposure, thus avoiding estrogenic influence outside the vagina [4,5,[16][17][18]54].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…19 It is also important to recognize that effects of sex hormones on sexual function, sexual thoughts and behaviour may be (at least partially) mediated indirectly through improved vaginal lubrication. 20 Of relevance in men, penile injury following intercourse reduces libido, and circumcision to prevent future penile injury is associated with recovery of libido. 21 A cross-sectional study of 1423 women between the ages of 18 and 75 suggested total testosterone measured via radioimmunoassay, calculated free testosterone, dehydroepiandrosterone sulphate and androstenedione declined steeply in the early reproductive years and do not vary as a consequence of natural menopause, and the postmenopausal ovary seems to be an ongoing site of testosterone production.…”
Section: Androg En S and Their Role In S E Xual Fun C Tionmentioning
confidence: 99%